Electronics for microwave backhaul - Camarchia, Vittorio; Quaglia, Roberto (Research associate); Pirola, Marco (Norwood : Artech House, 2016)
This timely new resource presents an overview of the electronics of mobile network backhaul. Infrastructure planning, architecture evolution, digital controls, and countermeasures are all presented highlighting the building blocks of specific backhaul features. Tx and Rx design and antenna requirements and covered while examining the overall construction of the microwave radio hardware blocks. Single blocks are explored: the antenna, the analog transmitter and receiver, and the modem, recalling the most important aspects of transport networks and microwave link dimensioning. Essential theory is provided for each hardware block with an emphasis on present solutions. Authored by academic and industrial experts in the field, development and design engineers will benefit from the practical guidance in solving realistic issues and providing useful tips throughout the design process. This book guides readers through the historical evolution of microwave radios and the components of the next generation of mobile networks.
1.4.4 Interference1.5 Description of Chapters; References; 2 Evolution of Microwave Radios; 2.1 Introduction; 2.2 Microwave versus Wired; 2.2.1 Benefits and Disadvantages of Microwave; 2.3 The Historical Evolution of Radio Links; 2.3.1 Microwave Pioneers; 2.3.2 Early Years from the 1920s to the 1940s; 2.3.3 The Microwave Industry; 2.3.4.
Description based on print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 072
Keywords: Microwave devices; Mobile communication systems; Cell phone systems; Cell phone systems; Microwave communication systems; Microwave devices; TECHNOLOGY & ENGINEERING / Mechanical; Electronic books; Electronic books